A militância em movimento: amizade e maquinação de modos de existência no MST - Leite, Jáder Ferreira (2008)
This study focuses on two issues, the process of subjectivity production and the exercise of friendship alongside political militancy in the Landless Rural Workers Movement (MST). Friendship is here understood as the social practice with the potential to question certain modes of socially formed relationships as well as their becoming a political exercise. The political militancy phenomenon is problematized based on the subjectivity production perspective. The objective of the study was to construct acartography of the subjectivity production processes with political activists of the MST and to highlight the points in which the exercise of friendship enhances the appearance of singularity in the context of this militancy. The cartography is a research method that permits the identification of macro political, as well as micro political forces that interfere in a psychosocial context, such as the MST. The participants were members of an MST group that participated in a Pedagogy course coordinated by the Department of Education of the Universidade Federal do Rio Grande do Norte. The other participants were militants involved in political formation activities at the social base, as well as in the other levels of the MST in the states of Rio Grande do Norte, Paraíba, Pernambuco, Ceará, Minas Gerais and Paraná. The results are linked to the oscillate incorporation of the landless identity model that occurs as a group of disciplinary strategies are put in practice in the political formation activities with militants, as well as the ways of model evation are formed. This occurs to the extent that new demands and forms of invested desires beyond the land object are incorporated in the MST. Such singular processes happen in three areas of the political exercise of friendship articulation: the masses, where there is a possibility for the MST to construct a new social collectivity; gender relations, where the socially destined space for women is redimensionized and; sexual diversity, which provokes the MST to follow its potential in questioning the actual hegemonic living modes. It is therefore considered that the MST has a great opportunity to become an important mediator of contemporary social and political struggles